Selecting reproducible elements in non-destructive portable X-ray fluorescence analysis of prehistoric and early historical ceramics from Korea. (February 2023) - Kim, Junkyu; Park, Jung-Woo; Kim, Hyunwoo; Oh, Yongje; Park, Jiyoung; Conte, Matthew; Kim, Jangsuk
Graphical abstract: Highlights: Prehistoric and early historical ceramics from Korea are analyzed by pXRF. Reliability of pXRF data is evaluated by comparison with other methods. Reproducible elements vary depending on pottery types. Abstract: The use of non-destructive portable X-ray Fluorescence (pXRF) analysis for provenance studies of ceramics requires careful evaluation of the quality of data and selection of reliably measured elements. In this study, we report pXRF data on prehistoric and early historical ceramics from South Korea and compare the results with those obtained by destructive conventional geochemical techniques to evaluate the reproducibility of pXRF-measured elemental concentrations. A total of 92 ceramic sherds from the Mumun Period (15-1C BCE), Proto-Three Kingdoms and Three Kingdoms periods (1C BCE – 7C CE), and Unified Silla Period (7C – 10C CE) were analyzed. The results show that for ceramics of the Mumun and Three Kingdoms periods, Si, K, Ti, Mn, Fe, Rb, Sr, Zr, and Ba are elements whose concentrations are reliably measured by non-destructive pXRF. However, for the Unified Silla ceramics, only Fe, Sr, and Ba showed high reproducibility, while Si, K, Ti, Rb, and Zr did not, possibly due to different surface treatments applied. It is suggested that reproducible elements vary depending on context, even in the same area. Since it is difficult to globally determine reliably meausred elements, pilot studies and the development of local protocols to select reproducible elements in given contexts are recommended prior to provenance studies.